Knockdown of Enhancer of Zeste Homolog 2 Affects mRNA Expression of Genes Involved in the Induction of Resistance to Apoptosis in MOLT-4 Cells - Naimi, Adel; Safaei, Sahar; Entezari, Atefeh; Solali, Saeed; Hassanzadeh, Ali (Anti-Cancer Agents in Medicinal Chemistry, 2020)
Background: The Enhancer of Zeste Homolog 2 (EZH2) is a subunit of the polycomb repressive complex 2 that silences the gene transcription via H3K27me3. Previous studies have shown that EZH2 has an important role in the induction of the resistance against the Tumor necrosis factor-Related Apoptosis-Inducing Ligand (TRAIL)-Induced Apoptosis (TIA) in some leukemia cells. Objective: The aim of this study was to determine the effect of silencing EZH2 gene expression using RNA interference on the expression of death receptors 4 and 5 (DR4/5), Preferentially expressed Antigen in Melanoma (PRAME), and TRAIL human lymphoid leukemia MOLT-4 cells. Methods: Quantitative RT-PCR was used to detect the EZH2 expression and other candidate genes following the siRNA knockdown in MOLT-4 cells. The toxicity of the EZH2 siRNA was evaluated using Annexin V/PI assay following the transfection of the cells by 80 pM EZH2 siRNA at 48 hours. Results: Based on the flow-cytometry results, the EZH2 siRNA had no toxic effects on MOLT-4 cells. Also, the EZH2 inhibition increased the expression of DR4/5 but reduced the PRAME gene expression at the mRNA levels. Moreover, the EZH2 silencing could not change the TRAIL mRNA in the transfected cells. Conclusion: Our results revealed that the down-regulation of EZH2 in MOLT-4 cells was able to affect the expression of important genes involved in the induction of resistance against TIA. Hence, we suggest that the silencing of EZH2 using RNA interference can be an effective and safe approach to help defeat the MOLT-4 cell resistance against TIA.
Keywords: Leukemia